The Effect of L-Arginine Supplementation on the Quality of Frozen Goat Semen - Fahlevi, Reza; Wahjuningsih, Sri; Ihsan, Mohammad Nur (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
Various attempts have been made to maintain the quality of semen by using diluents that are added with appropriate antioxidants to protect spermatozoa from cold shock and maintain the quality of spermatozoa, while the addition of antioxidants in the diluent is useful for suppressing free radical reactions. One of the substances that can be added to cement thinner is L-Argine. The mechanism of action of L-Argine is the same as that of an antioxidant, which is useful in inhibiting free radicals. Nitric Oxide contained in L-Arginine is an antioxidant so that it can inactivate superoxide produced by spermatozoa during the oxygen consumption process. Shelters were carried out 2 times a week with the artificial vaginal method, with 10 shelters during the study. The semen that will be used for research has a minimum individual motility requirement of 70% and a minimum mass motility of ++. The variables observed in this study were abnormalities, intact plasma membrane and intact acrosome cap on observations before freezing and post thawing. The results of the analysis of variance showed that L-Arginine supplementation had no significant effect (p>0.05) on abnormalities in the pre-freezing and post-thawing observations, L-Arginine supplementation had a significant effect (p<0.05) on the integrity of the plasma membrane and acrosome cap. on observation before freezing and post thawing.Keywords:  abnormalities, antioxidants, L-Argine, spermatozoa